Dual-Mode Biquadratic Filter Employing Second-Generation Voltage Conveyors DM Biquadratic Filter Employing VCIIs - Roongmuanpha, Natchanai; Mongkolwai, Pratya; Pukkalanun, Tattaya; Tangsrirat, Worapong (My University, 2024)
In this paper, a dual-mode biquadratic filter is suggested. The proposed filter employs two Second-Generation Voltage Conveyors (VCIIs) along with four resistors and two capacitors. The suggested filter can realize all five standard biquadratic filter functions such as lowpass (LP), bandpass (BP), highpass (HP), bandstop (BS), and allpass (AP) in both voltage-mode (VM) and current-mode (CM) without needing to modify its circuit structure. The quality factor (Q) and natural angular frequency (ωo) can be accurately and separately controlled through the passive component. It additionally offers the capability of providing the output voltage at the low-output impedance terminal in VM. The effects of the VCII non-idealities on the filter performance have been analyzed in detail. The proposed filter also offers low active and passive sensitivity features. Simulation results achieved with PSPICE software using TSMC CMOS 0.18 μm parameter have been validated and compared with the theoretical findings.
Keywords: biquadratic filter; dual-mode circuit; Second-Generation Voltage Conveyor (VCII)